A biological and ecological study of the invasive pufferfish Torquigener hypselogeneion (Bleeker 1852) [conspecific Torquigener flavimaculosus Hardy & Randall, 1983] in the Eastern Mediterranean - Aylin Ulman; Hasan Deniz Akbora; Ozgur Çanak; Elaine Chu; Burak Ali Çiçek; Hasan Ersönmez; Sinan Mavruk; Caner Enver Özyurt; Taner Yildiz; Amy Liu; Nazli Demirel; Daniel Pauly (Aquatic Invasions)
The highly toxic orange-spotted toadfish Torquigener hypselogeneion (Bleeker 1852) [conspecific Torquigener flavimaculosus Hardy & Randall, 1983] is now a very common invasive fish in the Eastern Mediterranean. Its small size, well under 20 cm, may have concealed the danger it represents, and little is known about its biology or ecology. Here, the spawning seasons, gonado- and hepato-somatic index and condition factors of T. hypselogeneion from 3 locations of the Eastern Mediterranean are presented, based on a total of 1360 individuals sampled, i.e., 216 from Finike, 817 from Fethiye (both Turkey), and 327 from Cyprus. Our results show that T. hypselogeneion is a carnivorous species that forages on sandy bottoms, with a preference for small invertebrates, especially the small invasive gastropod Cerithium scabridum, crustaceans (hermit crabs, other crabs and barnacles), and sea urchins; however, at least in some localities, they appear to forgo eating during their peak reproductive period. The parameters of the von Bertalanffy Growth Function for T. hypselogeneion in the Eastern Mediterranean were: asymptotic length = 17.4 cm (total length; TL) and K = 0.96 year-1, implying a longevity of about 4 years, while the mean length at first maturity was about 10 cm (TL) for both sexes. An average-sized adult female (13 cm TL, 45.7 g live weight) was found to contain 1,250 eggs per gram body weight. Based on its high invasiveness and negative impacts to ecology of the Eastern Mediterranean and the human health, we suggest that T. hypselogeneion should be listed as a priority invasive species and that its population closely monitored within the Mediterranean Sea.